Medicine shortages in Fiji: A qualitative exploration of stakeholders’ views - Walker, Josephine (PLoS One, 2017)
OBJECTIVES: Medicine access is a human right; yet, concerningly, there are international instances of shortages. Quantitative data has allowed WHO to propose global solutions; however, individualised understanding of specific regions is still required to work towards national solutions. Fiji has an established issue with medication supply and the aim of this study was to use qualitative methods to gain a fuller understanding of this context. METHODS: Semi-structured interviews were used to gain the perspective of key stakeholders involved in the Fijian medicine supply chain in regards to causes, impacts and possible solutions of medicine shortages. Thematic analysis was used to analyse the interview data. RESULTS: In total, 48 stakeholders participated and the information was synthesised into three main themes, causes, impacts and solutions and the sub-themes including; political, system and patient causes, adverse health effects on patients, professional dissatisfaction, monetary loss and loss of faith in the health system, workarounds, operation improvements, government intervention and education and training. CONCLUSIONS: The situation in Fiji is not dissimilar to other instances of shortages around the world and hence international solutions like that proposed by WHO are feasible; however, they must be modified to be uniquely Fijian to work in this context.